1871 Miss. Rev. Code 586 - (:unkn) unknown (My University, 1871)
Ch. 58, art. 29, § 2683: If any person shall be found hunting with a gun, or with dogs, on the Sabbath, or fishing in any way, he shall, on conviction thereof, be fined not less than five, nor more than twenty dollars.
Keywords: HUNTING REGULATION